2021
DOI: 10.1038/s42003-021-02674-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of rare molecular subclasses of hepatocellular carcinoma

Abstract: Primary liver cancer, consisting of both cholangiocarcinoma (CCA) and hepatocellular carcinoma (HCC), is the second leading cause of cancer deaths worldwide. Our goal is to genomically characterize rare HCC subclasses to provide insight into disease biology. Leveraging The Cancer Genome Atlas (TCGA) to perform a combined analysis of CCA (n = 36) and HCC (n = 275), we integrated multiple genomic platforms, to assess transcriptional profiles, mutational signatures, and copy number patterns to uncover underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Although several studies have identified important molecular classes in HCC, uncertainty remains regarding their associations with outcomes and their complex interaction with liver regenerative processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recently, our lab defined three distinct molecular-based subpopulations of HCC tumors, namely HCC, Blast-Like, and CCA-like, based on gene expression similarity to cholangiocarcinomas and hepatoblast cells [ 14 ]. The HCC class has prototypical HCC tumor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have identified important molecular classes in HCC, uncertainty remains regarding their associations with outcomes and their complex interaction with liver regenerative processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recently, our lab defined three distinct molecular-based subpopulations of HCC tumors, namely HCC, Blast-Like, and CCA-like, based on gene expression similarity to cholangiocarcinomas and hepatoblast cells [ 14 ]. The HCC class has prototypical HCC tumor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Annotations of tumor molecular subtyping from Damrauer et al revealed that this altered subset was enriched for blast-like and cholangiocarcinoma-like LIHC samples. 14 These two molecular subtypes were also observed among the unaltered samples (77/330, 23.3%). Blast-like and cholangiocarcinoma-like tumors also have BAP1 alteration signature scores higher than the other LIHC tumors (Figures 4A-B and Supplemental Table S3B, pairwise two-sided Mann-Whitney U test with continuity correction and Bonferroni adjusted p=3.96e-7 and p=5.54e-15 respectively).…”
Section: Bap1 Alteration Characterizes a Molecularly Distinct Subset ...mentioning
confidence: 83%
“…This work led to further investigations into the role of BAP1 mutations in promoting the development of cancer across multiple tissue types as well as the relation of BAP1 loss to differential survival outcomes. [11][12][13][14] BAP1 mutations are most prevalent in uveal melanoma, mesothelioma, and renal cell carcinoma. 1,15 Mutations occur very infrequently in other cancer types, often leading to exclusion from consideration due to underpowered analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPP1(the CD44 ligand) derived from activated hepatic stellate cells (HSC) serves as a stimulator for KLRG1+ NK cells that can mediate liver scarring limitation in CHB pathogenesis (Wijaya et al, 2019) and has predictive value in the prognosis of HCC (Shang et al, 2012;da Costa et al, 2015). SOX9, which can be directly induced in HBV-infected human hepatoma cells (Yang et al, 2020) has been identified as a risk factor for cirrhosis and HCC (Chen et al, 2021;Damrauer et al, 2021). However, these previous studies are performed just through flow cytometry (FCM), immune fluorescence (IF), and immunohistochemistry (IHC) with limited subpopulations of liver-infiltrating lymphocytes (LILs) and a small samples size; the orchestra of multiple chemokines and ECM related genes with a variety of LILs during HBV pathogenesis are not globally indicated.…”
Section: Introductionmentioning
confidence: 99%